Information security curriculum framework at undergraduate level - Sanusi Arifin, Ab. Arif (2009)
This study focuses on developing Information Security (IS) curriculum framework at undergraduate level. Qualitative technique is used in order to collect information and analyzed that information to obtain useful input for this study. Qualitative technique covers interview, and analyzing secondary sources. The acquired information is used to construct the framework by applying backward design curriculum model. It is an approach that begins with the desired outcomes and goals then, works backward to learning objectives grouped into courses. As a result, the proposed framework named as Information Security Curriculum framework at undergraduate level comprises of six learning outcomes with its core knowledge based on ten IS Common Body of Knowledge (CBK). The proposed framework is then verified according to Malaysia Qualification Framework (MQF) elements qualification.